Deskripsi Perkembangan Keterampilan Dasar Kerja Laboratorium Kimia Siswa SMA Negeri 1 Singaraja - Ketut Sepdyana Kartini (Hydrogen: Jurnal Kependidikan Kimia, 2019)
The aims of this study was to describe the development of basic skills students in achemistry laboratory carrying out the work. This study was conducted using a qualitative approachwith the subject of the research is 603 students consisting of 8 classes of X grade, 7 classes of XIgrade and 7 classes of XII grade. Data were collected with observation papers. The results showedonly 8 out of 10 aspects of the basic skills of laboratory work were observed. Five aspects of skillsclassified into very well categories and three categories of skills aspect quite well.